HUBUNGAN ANTARA STATUS GIZI DAN PAPARAN MEDIA MASSA DENGAN KEJADIAN MENARCHE DINI PADA SISWI SDN BAROKAH KECAMATAN SIMPANG EMPAT KABUPATEN TANAH BUMBU: THE RELATIONSHIP BETWEEN NUTRITIONAL KABUPATEN STATUS AND MASS MEDIA EXPOSURE AND THE INCIDENCE OF EARLY MENARCHE AMONG FEMALE STUDENTS AT SDN BAROKAH, SIMPANG EMPAT DISTRICT, TANAH BUMBU REGENCY - Jumria; Susanti, Novia; Putra, Farhandika (WELL BEING, 2025)
Early menarche refers to the onset of menstruation in girls before the age of 12, marking one of the first signs of puberty. This condition can be influenced by nutritional status and exposure to mass media. This study aimed to analyze the relationship between nutritional status and mass media exposure with the incidence of early menarche among female students. A quantitative method with a correlational analytic design and a cross-sectional approach was employed. The study involved 36 respondents selected using purposive sampling. Data were collected through questionnaires and anthropometric measurements. The results indicated that nearly half of the respondents (38.9%) experienced menarche at the age of 11, approximately one-third (33.2%) were at risk of being overweight, and almost all respondents (86.1%) were heavily exposed to mass media. A moderate correlation was found between nutritional status and early menarche (r = 0.412, p = 0.012), as well as between mass media exposure and early menarche (r = 0.451, p = 0.006). In conclusion, higher nutritional status and greater exposure to mass media are associated with an increased likelihood of early menarche. It is recommended that female students manage their diet by selecting nutritious foods and exercise caution when accessing mass media.